Campbell's urology - Walsh, Patrick C., 1938-; Campbell, Meredith F. (Meredith Fairfax), 1894-1968 (Philadelphia : Saunders, 2002)
Campbell's Urology has established a universal reputation as the'go to' resource for current, reliable guidance on any subject in the field including operative and pediatric urology
System requirements : Windows ; IBM PC or compatible, 486X or higher, Windows 95, 98, NT, ME, 2000, XP, 16 MB RAM (32 MB recommended), 10 MB of available hard-disk space, 2x or faster CD-ROM drive, color monitor with SVGA (800 x 600 resolution, 256 colors) or better
System requirements : Macintosh ; Apple Power Macintosh G3 or compatible computer, Mac OS 9 or later, 16 MB RAM (32 MB recommended), 10 MB of available hard-disk space, 2X or faster CD-ROM drive, color monitor with SVGA (800 x 600 resolution, 256 colors) or better
Keywords: Urogenital diseases; Urology -- methods